Influence of information technologies on technical fitness of students in sport-oriented physical education - Zh.L. Kozina; O.M. Ol'khovyj; V.A. Temchenko (Physical Education of Students)
Purpose: to determine influence of information technologies in sport-oriented physical education on technical fitness of students, practicing football indoors. Material: in the researches students (boys - n=40) of 18-20 years’ age participated. Standard tests on physical condition were used. For determination of motor skills and abilities we used: juggling with ball; kick in pre-set sector of goal; shuttle run 4 x 10 meters with dribbling; kick for distance. Results: structural model of sport-oriented students’ physical education with application of information technologies has been formed. In the model all students are trained in sport-oriented academic groups by chosen kinds of sports (motor functioning). Such approach envisages holistic form of program material construction and unified algorithm of students’ progress assessment. Conclusions: the wholeness of sport-oriented physical education’s functioning is ensured at the account of application of information technologies. It permits to optimize motor skills’ training process. In this case single form of building of program material is created.